Drosophila Tet Is Expressed in Midline Glia and Is Required for Proper Axonal Development - Ismail, Joy N.; Badini, Shireen; Frey, Felice; Abou-Kheir, Wassim; Shirinian, Margret (Frontiers in Cellular Neuroscience, 2019)
Ten-Eleven Translocation (TET) proteins are important epigenetic regulators that play a key role in development and are frequently deregulated in cancer. Drosophila melanogaster has a single homologous Tet gene (dTet) that is highly expressed in the central nervous system during development. Here, we examine the expression pattern of dTet in the third instar larval CNS and discovered its presence in a specific set of glia cells: midline glia (MG). Moreover, dTet knockdown resulted in significant lethality, locomotor dysfunction, and alterations in axon patterning in the larval ventral nerve cord. Molecular analyses on dTet knockdown larvae showed a downregulation in genes involved in axon guidance and reduced expression of the axon guidance cue Slit. Our findings point towards a potential role for dTet in midline glial function, specifically the regulation of axon patterning during neurodevelopment.